PREVALÊNCIA DE TRANSTORNOS DE ANSIEDADE EM PACIENTES COM FIBRILAÇÃO ATRIAL EM ACOMPANHAMENTO CARDIOLÓGICO - ARAKAKI, Matheus Willian; SANTANA, Leonardo Correia; BUENO, Bruno Barros; JABBOUR, Vitor; VERAS, André Barciela (ANAIS DO ENIC, 2020)
-